Aufnahme der Ausstellung Existential Phantasies - The Monkey on your Shoulder im Iwalewahaus (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2016)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Africa; Artists; Art; Photographs; Exhibitions; Art Exhibition; Iwalewahaus; Cultural Centre; Performing Arts Center; Art Collector; Art Collecting